Religious Pluralism and Identity Among Descendants of Bosnian Migrants in Slovenia - Ana Ješe Perković (Religions)
This article examines the religious practices of descendants of Bosnian migrants in Slovenia, a country that stands out as one of the most secular in Europe. While Bosnia and Herzegovina is known for its complex religious pluralism, where religious institutions play a crucial role in nation-building, Slovenia presents a contrasting context of secularization. Applying Peter Berger’s theory of religious pluralism, which suggests that pluralism weakens traditional religious authority, this study explores how descendants of Bosnian migrants navigate their religious identities in a secular environment. Although their identities have been shaped by the Yugoslav wars and the post-war redefinition of ethnicity through religion, younger generations are also influenced by broader social processes in Slovenia, including secularization, integration, and exposure to multiple belief systems. Using a qualitative research approach based on semi-structured interviews, this case study investigates the preservation and transformation of religious traditions among Bosnian migrant descendants and how these practices influence their identity. The findings highlight how migration and adaptation to a different socio-cultural environment shape religious practices across generations, contributing to broader discussions on religious choice, identity, and pluralism in contemporary societies.